Otimização do processo de microfiltração para a produção de suco de melancia - Lovato, Frederico (2019)
Watermelon (Citrullus lanatus) is a fruit originating from Africa that stands out as an important product of Brazilian agribusiness. Juice preservation processes traditionally involve the use of high temperatures leading to the degradation of beneficial and thermolabile substances such as antioxidant compounds, vitamin C and lycopene. Alternatively, the membrane separation processes that can be conducted under mild temperature conditions, ensuring high shelf life. The objective of the present work was to evaluate the influence of temperature and pressure in watermelon juice microfiltration process against permeate flow, lycopene, reducing sugars, phenolic compounds and flavonoids contents according to a complete factorial design of 22 with triplicate in the central point. Lycopene content increased with increasing pressure and temperature. The contents of phenolic and flavonoid compounds were influenced only by temperature variation. Using the function desirability, it was defined that the optimal process conditions, aiming at maximizing the variables under study would be at the pressure of 1.0 bar and temperature of 37 ºC. The concentrated juice reached a lycopene content 59.98% higher than in natura, besides an increase of 17.22 and 34.36% of phenolic and flavonoid compounds, respectively. There was a high mineral content in both concentrated juice and permeate fraction, showing commercial viability for both products. Despite a reduction compared to fresh juice, the concentrate had 3 times higher ascorbic acid content than the pasteurized, 15.03 and 5.00 mg L-1, respectively. Sensory analysis of the product revealed significant difference when compared to pasteurized juice, that is, consumers realized that the juice had been submitted to the microfiltration process. The taste acceptance was low: 66.89%, as well as Purchase Intent: 56% of tasters have doubts of purchase or claim that they would not buy the product, attributed to losses in taste-related non-volatile compounds during processing. From the obtained product, microbiological tests of total and thermotolerant coliforms, aerobic and mesophilic, molds and yeasts and Salmonella sp. were performed, demonstrating the microfiltration capacity to remove such microorganisms and, under refrigeration, to keep the juice suitable for consumption for a period of 14 days. The results obtained in this work show that the microfiltration processes were effective in the concentration of watermelon juice, increasing the concentration of lycopene, total reducing sugars, phenolic compounds and flavonoids, preserving their physicochemical and microbiological quality and can be used as an input for the production of food with functional characteristics.